1998
DOI: 10.1103/physrevb.57.2530
|View full text |Cite
|
Sign up to set email alerts
|

Ion implantation in GaN at liquid-nitrogen temperature: Structural characteristics and amorphization

Abstract: This paper deals with the results of a systematic investigation of damage generation and accumulation until amorphization induced by 180 keV Ca ϩ and Ar ϩ implantation in GaN films at liquid-nitrogen temperature. The structure of GaN films before and after implantation was characterized by Rutherford backscattering/ channeling, cross-sectional transmission electron microscopy, and high-resolution x-ray diffraction. The asimplanted GaN films exhibits an expanded lattice. Its texture was determined by pole figur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
47
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 24 publications
(29 reference statements)
10
47
0
1
Order By: Relevance
“…6͑a͒ that the damage buildup in GaN is highly sigmodal for the case of light ion bombardment. This behavior is consistent with the results of LN 2 temperature bombardment of GaN with intermediate mass ions ͓Si, 2 Ar, 6 and Ca ͑Ref. 6͔͒.…”
Section: A Bombardment With 40 Kev C Ionssupporting
confidence: 80%
See 2 more Smart Citations
“…6͑a͒ that the damage buildup in GaN is highly sigmodal for the case of light ion bombardment. This behavior is consistent with the results of LN 2 temperature bombardment of GaN with intermediate mass ions ͓Si, 2 Ar, 6 and Ca ͑Ref. 6͔͒.…”
Section: A Bombardment With 40 Kev C Ionssupporting
confidence: 80%
“…[2][3][4][5][6][7][8][9] This situation is surprising since such studies often give an insight into the important properties of the defects produced by an ion beam. For example, information on the mobility and effective lifetimes of defects, defect clustering efficiency, and on the influence of interfaces on mobile defects can often be obtained from an analysis of damage buildup under ion irradiation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recent ion-implantation studies [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have revealed that, unlike the situation for mature semiconductors such as Si and GaAs, GaN exhibits a range of intriguing behavior involving extreme property changes under ion bombardment. 19 In particular, it has been shown that dynamic annealing processes ͑i.e., defect-interaction processes͒ in GaN are extremely efficient even during heavy-ion bombardment at liquid-nitrogen temperature.…”
Section: Introductionmentioning
confidence: 99%
“…For the as-implanted GaN, early studies [5][6][7] have reported on some typical features: planar defects, and an amorphous layer which formed on top of GaN. The planar defects have been observed to be the most characteristic defects in GaN bombarded with ions in a wide range of implantation conditions, independently of the ion, fluence, energy, and implantation temperature.…”
Section: Introductionmentioning
confidence: 99%